Internet of things: security requirements, attacks and counter measures - Maria Imdad; Deden Witarsyah Jacob; Hairulnizam Mahdin; Zirawani Baharum; Shazlyn Milleana Shaharudin; Mohd Sanusi Azmi (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
Internet of Things (IoT) is a network of connected and communicating nodes. Recent developments in IoT have led to advancements like smart home, industrial IoT and smart healthcare etc. This smart life did bring security challenges along with numerous benefits. Monitoring and control in IoT is done using smart phone and web browsers easily.  There are different attacks being launched on IoT layers on daily basis and to ensure system security there are seven basic security requirements which must be met. Here we have used these requirements for classification and subdivided them on the basis of attacks, followed by degree of their severity, affected system components and respective countermeasures. This work will not only give guidelines regarding detection and removal of attacks but will also highlight the impact of these attacks on system, which will be a decision point to safeguard  system from high impact attacks on priority basis.